Optogenetic Control of the Canonical Wnt Signaling Pathway During Xenopus laevis Embryonic Development. Issue 18 (3rd September 2021) - Krishnamurthy, Vishnu V.; Hwang, Hyojeong; Fu, Jia; Yang, Jing; Zhang, Kai
Graphical abstract: Highlights: Light-dependent cytoplasm-to-membrane translocation of LRP6 activates canonical Wnt signaling. Optogenetic activation of OptoLRP6opt results in axis duplication in Xenopus laevis. Axis duplication results from the formation of ectopic Spemann Organizer. Abstract: Optogenetics uses light-inducible protein-protein interactions to precisely control the timing, localization, and intensity of signaling activity. The precise spatial and temporal resolution of this emerging technology has proven extremely attractive to the study of embryonic development, a program faithfully replicated to form the same organism from a single cell. We have previously performed a comparative study for optogenetic activation of receptor tyrosine kinases, where we found that the cytoplasm-to-membrane translocation-based optogenetic systems outperform the membrane-anchored dimerization systems in activating the receptor tyrosine kinase signaling in live Xenopus embryos. Here, we determine if this engineering strategy can be generalized to other signaling pathways involving membrane-bound receptors. As a proof of concept, we demonstrate that the cytoplasm-to-membrane translocation of the low-density lipoprotein receptor-related protein-6 (LRP6), a membrane-bound coreceptor for the canonical Wnt pathway, triggers Wnt activity. Optogenetic activation of LRP6 leads to axis duplication in developing Xenopus embryos, indicating that the cytoplasm-to-membrane translocation of the membrane-bound receptor could be a generalizable strategy for the construction of optogenetic systems.